Assessing rugby place kick performance from initial ball flight kinematics: development, validation and application of a new measure. Issue 5 (3rd September 2019) - Atack, Alexandra; Trewartha, Grant; Bezodis, Neil E.
Abstract: The appropriate determination of performance outcome is critical when appraising a performer's technique. Previous studies of rugby place kicking technique have typically assessed performance based on ball velocity, but this is not the sole requirement. Therefore, a mathematical model of rugby place kick ball flight was developed to yield a single measure more representative of true performance. The model, which requires only initial ball flight kinematics, was calibrated and validated using empirical place kick data, and found to predict ball position with a mean error of 4.0% after 22 m of ball flight. The model was then applied to the performances of 33 place kickers. The predicted maximum distance, a single performance measure which accounted for initial ball velocity magnitude and direction, and spin, was determined using the model and was compared against ball velocity magnitude. A moderate association in the rank-order of the kicks between these two measures ( ρ  = 0.52) revealed that the relative success of the kicks would be assessed differently with each measure. The developed model provides a representative measure of place kick performance that is understandable for coaches, and can be used to predict changes in performance outcome under different ball launch or environmental conditions.